Entrepreneurial Leadership and Employee Wellbeing During COVID-19 Crisis: A Dual Mechanism Perspective - Bilal, Muhammad; Chaudhry, Shafaq Arif; Sharif, Imran; Shafique, Owais; Shahzad, Khurram (Frontiers in Psychology, 2022)
This research studied the potential impacts of entrepreneurial leadership on followers’ psychological well-being and proactive work behaviour through sustainable employability and work uncertainty in a sample of 218 employees employed in SMEs of Pakistan . Hierarchical regression results demonstrated that entrepreneurial leadership was positively connected with sustainable employability and negatively linked with work uncertainty. Sequentially, sustainable employability was positively correlated with proactive work behaviour, employees’ psychological well-being, and work uncertainty negatively associated with proactive work behaviour and employees’ psychological well-being During COVID-19 Crisis . Furthermore, bootstrapping confirmed the mediation effects of work uncertainty and sustainable employability on proactive work behavior and the psychological well-being of employees except sustainable employability which did not mediate the relationship between entrepreneurial leadership and psychological well-being. Mediators, Sustainable employability, and work uncertainty positively linked employees’ psychological well-being and proactive work behaviour. The results highlighted the significant roles of sustainable employability and work uncertainty and interpreted why entrepreneurial leadership may result in employees’ positive behaviours.